Nanometer-resolved mechanical properties around GaN crystal surface steps - Buchwald, Jörg; Sarmanova, Marina; Rauschenbach, Bernd; Mayr, Stefan G. (Beilstein Journal of Nanotechnology, 2014)
The mechanical properties of surfaces and nanostructures deviate from their bulk counterparts due to surface stress and reduced dimensionality. Experimental indentation-based techniques present the challenge of measuring these effects, while avoiding artifacts caused by the measurement technique itself. We performed a molecular dynamics study to investigate the mechanical properties of a GaN step of only a few lattice constants step height and scrutinized its applicability to indentation experiments using a finite element approach (FEM). We show that the breakdown of half-space symmetry leads to an “artificial” reduction of the elastic properties of comparable lateral dimensions which overlays the effect of surface stress. Contact resonance atomic force microscopy (CR-AFM) was used to compare the simulation results with experiments.
Keywords: finite elements; gallium nitride; indentation; mechanical properties; molecular dynamics; nanostructures

(untitled) - Rabe, U.; Arnold, W. (Appl. Phys. Lett., 1994)

(untitled) - Yamanaka, K.; Ogiso, H.; Kolosov, O. (Appl. Phys. Lett., 1994)

APS March Meeting 2010 - Stan, G.; Cook, R. (Elastic property characterization of oxidized Si nanowires by contact-resonance atomic force microscopy, Portland, Oregon, USA, 15.3.2010-19.3.2010, 2010)

(untitled) - Stan, G.; Ciobanu, C. V.; Parthangal, P. M.; Cook, R. F. (Nano Lett., 2007)

(untitled) - Stan, G.; Cook, R. F. (Nanotechnology, 2008)

(untitled) - Izumi, S.; Hara, S.; Kumagai, T.; Sakai, S. (Thin Solid Films, 2004)

(untitled) - Morkoç, H.; Strite, S.; Gao, G. B.; Lin, M. E.; Sverdlov, B.; Burns, M. (J. Appl. Phys., 1994)

(untitled) - Nakamura, S.; Senoh, M.; Mukai, T. (Appl. Phys. Lett., 1993)

(untitled) - Held, R.; Nowak, G.; Ishaug, B. E.; Seutter, S. M.; Parkhomovsky, A.; Dabiran, A. M.; Cohen, P. I.; Grzegory, I.; Porowski, S. (J. Appl. Phys., 1999)

(untitled) - Weyher, J. L.; Brown, P. D.; Zauner, A. R. A.; Müller, S.; Boothroyd, C. B.; Foord, D. T.; Hageman, P. R.; Humphreys, C. J.; Larsen, P. K.; Grzegory, I.; Porowski, S. (J. Cryst. Growth, 1999)

(untitled) - Steiner, P.; Gnecco, E.; Krok, F.; Budzioch, J.; Walczak, L.; Konior, J.; Szymonski, M.; Meyer, E. (Phys. Rev. Lett., 2011)

(untitled) - Holland-Moritz, E.; Gordon, J.; Borges, G.; Sonnenfeld, R. (Langmuir, 1991)

Understanding Molecular Simulation: From Algorithms to Applications - Frenkel, D.; Smit, B. (Elsevier Science, 2001)

(untitled) - Plimpton, S. (J. Comput. Phys., 1995)

(untitled) - Béré, A.; Serra, A. (Philos. Mag., 2006)

(untitled) - Nosé, S. (J. Chem. Phys., 1984)

(untitled) - Hoover, W. G. (Phys. Rev. A, 1985)

COMSOL Multiphysics (COMSOL, Inc., 2010)

(untitled) - Polian, A.; Grimsditch, M.; Grzegory, I. (J. Appl. Phys., 1996)

(untitled) - Vlassak, J. J.; Nix, W. D. (Philos. Mag. A, 1993)

(untitled) - Barnett, D.; Lothe, J. (Phys. Norv., 1975)

On the elastic properties of nanocrystalline materials and the determination of elastic properties on a nanoscale using the atomic force acoustic microscopy technique - Kopycinska-Müller, M. (Universität des Saarlandes, 2005)

(untitled) - Steiner, P.; Roth, R.; Gnecco, E.; Glatzel, T.; Baratoff, A.; Meyer, E. (Nanotechnology, 2009)

(untitled) - Neumann, L.; Gerlach, J. W.; Rauschenbach, B. (Thin Solid Films, 2012)

(untitled) - Jakob, A. M.; Müller, M.; Rauschenbach, B.; Mayr, S. G. (New J. Phys., 2012)

(untitled) - Jakob, A. M.; Buchwald, J.; Rauschenbach, B.; Mayr, S. G. (Nanoscale, 2014)